Increased ferritin, serum lactate dehydrogenase, and aspartate aminotransferase levels predict macrophage activation syndrome complicating systemic lupus erythematosus: a retrospective study - Yingying Liu; Yuting Pan; Jing Jin; Panpan Wang; Tonghao Zhang; Zhidan Fan; Haiguo Yu (Frontiers in Pediatrics)
BackgroundThis study aimed to assess the diagnosis of macrophage activation syndrome (MAS) at the onset of active childhood-onset systemic lupus erythematosus (cSLE), which is under-researched, and to compare the characteristics of cSLE with and without MAS, hypothesizing the existence of possible predictors of MAS in active cSLE.MethodsThis study enrolled 157 patients diagnosed with cSLE, with or without MAS, from Nanjing Medical University between January 2018 and May 2023. Data analysis was performed using an independent samples t-test or the Mann–Whitney U-test, the χ2 test, the Youden index to determine the optimal cutoff values for diagnosis, and binary logistic regression analysis to determine the predicted probability.ResultsFifteen patients (9%) had MAS in the active phase, with an SLE disease activity index of 16.6 (range, 6–32). Bone marrow aspirations revealed hemophagocytosis in 8/15 cases (53%). Fever was the most common feature of MAS patients. Lactate dehydrogenase (LDH) and ferritin levels were elevated in the patients. Lower leukocyte, neutrophil, and platelet counts, including serum sodium and fibrinogen, and increased alanine aminotransferase, aspartate aminotransferase (AST), lactate dehydrogenase (LDH), ferritin, triglyceride, and D-dimer levels occurred in MAS patients, unlike those without MAS. Optimal cutoff values for ferritin (≥607.35 ng/ml), LDH (≥424 U/L), and AST (≥61 U/L) were predictors of MAS occurrence in cSLE. No MAS patients experienced recurrence during an 18-month mean follow-up.ConclusionsDespite the narrow scope of the study, elevated levels of ferritin, LDH, and AST may represent indicators of cSLE complicated by MAS. Early diagnosis and treatment may improve outcomes.